A new selective blood agar medium for Streptococcus pyogenes and other haemolytic streptococci - Lowbury, E. J. L. (1964)
Horse blood agar containing polymyxin B sulphate, neomycin sulphate, and fusidic acid inhibited the growth of Staph. aureus, Ps. pyocyanea, Proteus mirabilis, E. coli, and Klebsiella pneumoniae but allowed good growth of, and haemolysis by, Str. pyogenes. In a comparison with blood agar, blood 4% agar, and gentian violet blood agar, the selective medium (P.N.F.) yielded a significantly higher proportion of streptococci than the other media, both by aerobic and by anaerobic culture, from burn swab extracts deliberately contaminated with Str. pyogenes; P.N.F. culture was more effective with dilute than with heavy inocula of Str. pyogenes, allowing from three to seven times as many recoveries of Str. pyogenes from swabs contaminated with 10(−3) dilution of streptococcal cultures than cultures of the same material on the other media. Haemolytic streptococci of groups A, C, D, G, and others were isolated by aerobic culture from burns in a consecutive series of 1,277 swabs more often on P.N.F. medium than on blood 4% agar. Viable counts of 12 strains (including 11 different serological types) of Str. pyogenes showed some reduction in the numbers of colonies compared with counts on blood agar, and some strains grew more slowly on P.N.F. medium. These limitations, however, were offset and outweighed by the higher final yield of streptococci on the selective medium.